TEACHING PRACTICE AT A RURAL SCHOOL? AND WHY SHOULD WE GO THERE? - DE LANGE, NAYDENE; KHAU, MATHABO; ATHIEMOOLAM, LOGAN (South African Journal of Higher Education, 2016)
The National Framework for Quality Education in Rural Areas (DoE 2006) draws attention to education in rural ecologies and scrutinises the role of HEIs in developing teachers who understand the diverse contexts and who are able to facilitate quality teaching and learning in such contexts. This article explores how a teaching practice programme at a rural school can contribute to creating a sustainable learning environment, and cultivate a democratic citizenry. The paper draws on work done in the project New teachers for new times: Visual methodologies for social change in rural education in the age of AIDS, and argues that when pre-service teachers are taken out of their comfort zones to teach as a cohort in a school in a rural context, where they are enabled and supported by teacher-educators through daily debriefing and reflection, a shift in their thinking about teaching and about themselves as teachers and democratic citizens can occur. Key words: rural school, teaching practice, student teachers, democratic citizenry, rural ecology